Case studies on suppression of multimodal electromechanical oscillations by statcom's supplementary controller - Razali N.M.; Ramachandaramurthy V.K.; Mukerjee R.N. (2023)
STATCOM is primarily employed to manage reactive power at crucial locations in power system. Earlier studies have indicated the feasibility of equipping STATCOM with a supplementary controller to act as a damper for power swings. The paper outlines a STATCOM controller model and residue-based tuning method for its supplementary controller. The paper also demonstrates the performance of the developed model in suppressing observable and controllable modes of electromechanical oscillations in a 2-area power system.